Summary of past experimental work in sheep and goat management, breeding and health at National Animal Husbandry Research Station, Naivasha, Kenya - Rouse, J.E. (University of Oklahoma Press, 1973)
Give a general summary of cattle breeds of the world by region. Topical discussions on livestock management practices; marketing and slaughterhouse facilities; animal diseases; government policies on livestock industry and prospect for cattle raising in numerous countries in the world included.